Obstacle Jump Game in Stimulating Gross Motor Skills of Early Childhood - Ramlah Yusran; Arie Martuty; Sahrul Syawal; Sutra Awaliyah Darfin; Usman Usman (PG PAUD Universitas Islam Makassar | LP2M-UIM | PPJ PAUD (Perhimpunan Pengelola Jurnal PAUD) Indonesia, 2026)
The development of gross motor skills in early childhood currently faces challenges due to an increasing sedentary lifestyle and gadget dependency, which impact the weakening of children's balance and physical coordination. This study aims to analyze the effect of the obstacle jump game on improving the gross motor skills of children aged 5–6 years in kindergarten. The research method used is quantitative with a quasi-experimental design of a pretest-posttest type without a control group. The research sample consisted of 20 children determined through a purposive sampling technique. Gross motor skills were measured through five main indicators, namely the ability to jump without assistance, running and jumping over obstacles, balance upon landing, movement coordination, as well as the children's courage and initiative. The intervention was carried out in a structured manner through six sessions of the obstacle jump game designed adaptively starting from the warming-up phase, gradual introduction of obstacles, to the cooling-down session. The data collection instrument was an observation sheet, while data analysis used the paired sample t-test assisted by SPSS version 23. The analysis results showed a t-value of 18.965 with a significance of 0.000 (p<0.05), indicating a significant increase in gross motor skills after the intervention was given. These findings indicate that the obstacle jump game is effective as a method of physical stimulation. This activity supports aspects of courage, body coordination, and children's active involvement in enjoyable physical activities, making it highly feasible to be integrated into early childhood education learning programs.